Protopanaxadiol stimulates glucose consumption by modulating the AMP-activated protein kinase pathway in myotubes, hepatoma cells, and adipocytes. - Dahae Lee; Sang Hee Shim; Ki Sung Kang (PLoS ONE, 2025)
Ginsenosides, the main active constituents of Panax ginseng, possess potent anti-diabetic and anti-obesity properties. In this study, we investigated the molecular and cellular mechanisms underlying the effects of protopanaxadiol (PPD), Rg3, Rb2, Re, Rc, Rh2, Rb1, Rg1, and compound K on palmitic acid (PA)-induced lipid accumulation in HepG2 hepatoma cells and glucose consumption (GC) in C2C12 myotubes and 3T3-L1 adipocytes. PA-induced lipid accumulation was determined using lipid (Oil Red O) staining. GC was performed using a 2-deoxy glucose based colorimetric GC kit. Protein expression was examined by western blot analysis. PPD, Rg1, Rb2, and Rg3 inhibited lipid accumulation in PA-treated HepG2 cells. PA significantly decreased lipid levels in HepG2 cells, which was prevented by PPD, Rg1, Rb2, and Rg3. PPD, Re, Rb1, and compound K enhanced PA-induced GC inhibition in 3T3-L1 cells, while PPD, Rg3, Rc, and Rh2 enhanced PA-induced GC inhibition in C2C12 cells. PA also significantly decreased the phospho-phosphoinositide 3-kinase, phospho-Akt, phospho- AMP-activated protein kinase α, and phospho-glycogen synthase kinase-3β levels as well as increased glycogen synthase, glucose-6-phosphatase, and phosphoenolpyruvate carboxykinase phosphorylation in all three cell lines, which were prevented by PPD. PPD may be a potential drug candidate that can stimulate GC in key insulin-sensitive tissues, such as the skeletal muscle, liver, and adipose tissue.